14-3-3γ binds regulator of G protein signaling 14 (RGS14) at distinct sites to inhibit the RGS14:Gα(i)–AlF(4)(−) signaling complex and RGS14 nuclear localization - Gerber, Kyle J. (J Biol Chem, 2018)
Regulator of G protein signaling 14 (RGS14) is a multifunctional brain scaffolding protein that integrates G protein and Ras/ERK signaling pathways. It is also a nucleocytoplasmic shuttling protein. RGS14 binds active Gα(i/o) via its RGS domain, Raf and active H-Ras–GTP via its R1 Ras-binding domain (RBD), and inactive Gα(i1/3) via its G protein regulatory (GPR) domain. RGS14 suppresses long-term potentiation (LTP) in the CA2 region of the hippocampus, thereby regulating hippocampally based learning and memory. The 14-3-3 family of proteins is necessary for hippocampal LTP and associative learning and memory. Here, we show direct interaction between RGS14 and 14-3-3γ at two distinct sties, one phosphorylation-independent and the other phosphorylation-dependent at Ser-218 that is markedly potentiated by signaling downstream of active H-Ras. Using bioluminescence resonance energy transfer (BRET), we show that the pSer-218–dependent RGS14/14-3-3γ interaction inhibits active Gα(i1)–AlF(4)(−) binding to the RGS domain of RGS14 but has no effect on active H-Ras and inactive Gα(i1)–GDP binding to RGS14. By contrast, the phosphorylation-independent binding of 14-3-3 has no effect on RGS14/Gα(i) interactions but, instead, inhibits (directly or indirectly) RGS14 nuclear import and nucleocytoplasmic shuttling. Together, our findings describe a novel mechanism of negative regulation of RGS14 functions, specifically interactions with active Gα(i) and nuclear import, while leaving the function of other RGS14 domains intact. Ongoing studies will further elucidate the physiological function of this interaction between RGS14 and 14-3-3γ, providing insight into the functions of both RGS14 and 14-3-3 in their roles in modulating synaptic plasticity in the hippocampus.